SYNTHESIS, CHARACTERIZATION AND ANTIMICROBIAL SCREENING OF NEW NICKEL (II) METAL COMPLEXES INCORPOATING SCHIFF BASES (CAHIERS MAGELLANES-NS, 2024)
In this, research four Schiff bases ligand (L1-L4) and its Ni (II) Complexes (CL1-CL4) synthesized and characterized. These complexes were synthesized using the ligands listed above and NiCl2.6H2O in a 1:1 stoichiometric ratio. Synthesized ligands were characterized by using 1H NMR, 13C NMR, UV-Visible, FT-IR, and HRMS techniques. The Ni (II) complexes were characterized by using UV-Visible, FT-IR, and TGA techniques. These complexes and ligands exhibit significant antibacterial activity over four distinct human pathogenic bacterial strains such as gram-negative Escherichia coli, Pseudomonas aeruginosa, and gram-positive Staphylococcus aureus and Bacillus substilis whereas antifungal activity against Candida albicans and Aspergillus niger fungal strains.